How do you evaluate \frac { 2x ^ { 2} + 2x } { 2x ^ { 2} } \cdot \frac { x ^ { 2} - 3x } { x ^ { 2} - 2x - 3}?
2 Answers
Jan 14, 2018
1
Explanation:
Jan 14, 2018
Explanation:
"factorise and cancel common factors where possible"
2x^2+2x=2x(x+1)larrcolor(blue)"common factor of 2x"
x^2-3x=x(x-3)larrcolor(blue)"common factor of x"
x2-2x-3=(x-3)(x+1)larrcolor(blue)"quadratic factorising"
rArr(2x^2+2x)/(2x^2)xx(x^2-3x)/(x^2-2x-3)
=(cancel(2x)cancel((x+1)))/(cancel(2x)cancel(x))xx(cancel(x)cancel((x-3)))/(cancel((x-3))cancel((x+1)))
=1xx1=1